Electronic marketing / Choo Sin Yong - Choo, Sin Yong (2001)
In the world of twenty-first-century business, enterprise resource planning (ERP) and Internet technologies are rapidly coming together. ERP software is used to share accurate information with trading partners. Meanwhile, Internet help to connect people, streamline processes and help reduce costs. Easy-to-use, web-based business environments help companies get to the point, and focus on what they do best. Integrated Business Solutions (IBS) developed under ERP concept, which enables the company for managing their daily business processes systematically. IBS consists eight modules that meet the needs of customers, suppliers, partners and employees. The eight modules are E-Human Resource, E-Supplier, E-Banking, E-Sales, E-Marketing, E-Inventory, E-Account and E-Office. Each module plays the important role in this ERP project. E-Marketing system is a web-based product information system. It serves as a centralized portal for people to look for product related information. This system is accommodating to users from different levels. E-Marketing system contains two sub-modules; that are consumer module and personnel module. Using different login identity, users will be accessing to either consumer's function and interface or personnel's function and interface. For the consumer module, users can get the related product information they want and give their feedback and personal information to company. For the personnel module, it provides the template for maintain the online catalog and also generating the consumer info and reports. Waterfall methodology has been chosen as the system development methodology for E-Marketing system. Meanwhile, the development tools for this system are Active Server Pages, Microsoft Visual InterDev 6.0, HTML, VBScript, JavaScript and Microsoft SQL Server 7.0. Windows 2000 chosen as the platform for this system, indirectly Internet Information Server become the web server during the development.